Iron Man 3 [videorecording (Blu-Ray + DVD)] - Tyler, Brian (Composer) (2013)
When Tony Stark (aka Iron Man) finds his entire world reduced to rubble, he must use all his ingenuity to survive, destroy his enemy, and somehow protect those he loves. But a soul-searching question haunts him, does the man make the suit, or does the suit make the man?